Anti-metal catalytic cracking catalyst and preparation method thereof

By using boron-phosphoraluminum composition in catalytic cracking catalysts, forming a mesoporous structure and fixing boron and AlPO4, the problem of catalyst contamination on metals such as nickel, vanadium, and iron is solved, and a high activity and stability of metal-resistant catalyst is achieved.

CN119869607AActive Publication Date: 2025-04-25PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311378056.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

Existing catalytic cracking catalysts are difficult to resist metal contamination such as nickel, vanadium, and iron at the same time, resulting in a decrease in catalyst activity and impairment of stability.

Method used

Boron phosphorus aluminum composition (a mixture of AlPO4 and B, P, Al) is used as an additive component to form a mesoporous structure by calcination, fix boron in the pores of the composition, inhibit the toxic effects of nickel and vanadium, and fix iron through AlPO4 to improve the metal resistance of the catalyst.

Benefits of technology

The catalyst is effectively resisted by the pollution of metals such as nickel, vanadium, and iron, maintains high activity and stability, reduces the yield of hydrogen and coke, and improves the yield of high-value-added products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004509466700000061
    Figure BDA0004509466700000061
  • Figure BDA0004509466700000081
    Figure BDA0004509466700000081
  • Figure BDA0004509466700000131
    Figure BDA0004509466700000131
Patent Text Reader

Abstract

The invention discloses an anti-metal catalytic cracking catalyst and a preparation method thereof. The preparation method comprises the following steps: mixing a first raw material with water, and pulping; adding a rare earth compound and a dispersing agent into the slurry, and uniformly stirring; and then carrying out spray forming, roasting, washing and drying to obtain the catalytic cracking catalyst, the first raw material comprises a boron-phosphorus-aluminum composition, a molecular sieve, clay and a binder; the boron-phosphorus-aluminum composition is a mixture of AlPO4, B, P and Al, and is subjected to roasting treatment in the preparation process. The obtained catalytic cracking catalyst can resist pollution of metals such as nickel, vanadium and iron at the same time, and has high activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic cracking catalysts, and in particular to a metal-resistant catalytic cracking catalyst and a preparation method thereof. Background Art

[0002] Catalytic cracking (FCC) is still an important processing method of catalytic cracking and still occupies an important position in refineries. In recent years, with the increasing depletion of oil resources, many refineries' catalytic cracking units have begun to process inferior and heavy raw materials for economic benefits. These heavy raw oils often contain metals such as nickel, vanadium, iron, sodium, and calcium. These metals often deposit on catalytic cracking catalysts, causing irreparable damage to the catalysts, thereby affecting the operation of the entire catalytic cracking process.

[0003] Among these metals, nickel, vanadium and iron have the greatest impact on the catalyst. Vanadium will form vanadic acid under the action of high-temperature water vapor, which will cause the molecular sieve in the catalyst to dealuminate and the catalyst activity to decrease. The toxicity of nickel is manifested in a strong catalytic dehydrogenation effect, which makes the selectivity of the catalytic cracking reaction worse and increases the yield of hydrogen and catalytic coke (coke generated by the catalytic cracking reaction on the acid center). At the same time, the presence of nickel will also aggravate the destructive effect of vanadium on the molecular sieve. The presence of iron metal is mainly manifested in the formation of a eutectic body with low-melting point components, forming iron nodules on the catalyst surface, and blocking the pores of the catalyst.

[0004] In order to reduce the toxic effects of such metals on catalysts, various processes and technologies have been developed to resist such hazards. Among them, catalytic cracking catalysts are the core of catalytic cracking process technology, and improving the technology to increase the anti-metal function of the catalyst is the most direct and effective way. However, the prior art rarely mentions the preparation technology of catalytic cracking catalysts that can resist metal pollution such as nickel, vanadium, and iron. Summary of the invention

[0005] The object of the present invention is to provide a metal-resistant catalytic cracking catalyst and a preparation method thereof. The catalytic cracking catalyst can resist metal pollution such as nickel, vanadium, iron, etc. at the same time and has high activity and stability.

[0006] The present invention prepares a boron-phosphorus-aluminum composition, and adds the composition as an additive component into a catalytic cracking catalyst to prepare a catalytic cracking catalyst that is simultaneously resistant to metal pollution such as nickel, vanadium, and iron. The composition is a mixture of AlPO4, B, P, and Al. The presence of the B element can effectively inhibit the pollution of nickel metal, and AlPO4 can effectively inhibit the dealumination of molecular sieves, thereby offsetting the poisoning effect of B on the catalyst.

[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a method for preparing a metal-resistant catalytic cracking catalyst, comprising the following steps:

[0009] The first raw material is mixed with water and slurried; a rare earth compound and a dispersant are added to the slurry and stirred evenly; and then the catalytic cracking catalyst is obtained by spray molding, roasting, washing and drying;

[0010] The first raw material includes a boron-phosphorus-aluminum composition, a molecular sieve, clay and a binder;

[0011] The boron-phosphorus-aluminum composite is a mixture of AlPO4 and B, P, and Al, and is calcined during the preparation process.

[0012] According to the preparation method of the present invention, preferably, the first raw material also includes pseudo-boehmite.

[0013] According to the preparation method of the present invention, preferably, the boron-phosphorus-aluminum composition is prepared by reacting an aluminum compound, phosphoric acid, and a boron compound and calcining at 400-700°C;

[0014] The boron compound is added according to the boron content of the total mass of the boron-phosphorus-aluminum composition of 2wt% to 6wt%, preferably 2wt% to 4wt%;

[0015] The aluminum compound and phosphoric acid are added in a molar ratio of Al:P of (0.5-2.0):1, preferably (0.9-1.5):1.

[0016] According to the preparation method of the present invention, preferably, the boron-phosphorus-aluminum composition is prepared by the following method 1 or method 2:

[0017] Method 1: Add aluminum compound to water, then add phosphoric acid dropwise; then add boron compound and stir to obtain a sol containing boron, phosphorus and aluminum;

[0018] Drying the sol containing boron, phosphorus and aluminum, and calcining at 400-700° C. for 1 h-4 h to obtain the boron-phosphorus-aluminum composite;

[0019] Method 2: adding an aluminum compound to water, and then dropping phosphoric acid to obtain a sol containing phosphorus and aluminum; drying the sol containing phosphorus and aluminum to obtain an intermediate product;

[0020] The boron compound is dissolved in water, loaded in the intermediate product by an impregnation method, dried, and calcined at 400 to 700° C. for 1 to 4 hours to obtain the boron-phosphorus-aluminum composite.

[0021] In the preparation process of the boron-phosphorus-aluminum composition of the present invention, a mesoporous structure is formed through calcination, and boron is fixed in the pores of the composition. During the preparation process of the catalyst, it is not easy to migrate to the surface of the molecular sieve to destroy the skeleton structure of the molecular sieve, so that the catalyst can maintain a relatively high activity stability; the formed mesoporous phosphorus-aluminum structure can effectively reduce iron pollution.

[0022] In method 1 and method 2, the calcination temperature is preferably 400-700° C., and the time is preferably 1-4 hours. In addition, the drying temperature is 80-120° C., and the time is 5-24 hours.

[0023] In the preparation process of the boron-phosphorus-aluminum composition of the present invention, in method 1 and method 2, after the phosphoric acid is added dropwise, aging can be carried out under stirring for a period of time, for example, 1 to 5 hours. In method 1, stirring is preferably continued for 0.5 to 3 hours after the boron compound is added. In the preparation process of the boron-phosphorus-aluminum composition, preferably, the aluminum compound is selected from one or a combination of two or more of aluminum oxide, pseudo-boehmite, aluminum nitrate, and aluminum chloride.

[0024] In the process of preparing the boron-phosphorus-aluminum composition, preferably, the concentration of the phosphoric acid is 20 wt % to 85 wt %, more preferably 30 wt % to 70 wt %.

[0025] In the process of preparing the boron-phosphorus-aluminum composition, preferably, the boron compound is a soluble boron compound selected from one or a combination of two or more of boron phosphate, boric acid, boric anhydride, ammonium borate, and ammonium fluoroborate.

[0026] In the catalytic cracking catalyst preparation process, preferably, the specific preparation process of the catalytic cracking catalyst includes:

[0027] Adding a second raw material into water, mixing evenly, and then adding a binder after aging to form a catalyst matrix slurry; the second raw material is part of the components in the first raw material, including the boron-phosphorus-aluminum composition and clay, or the second raw material includes the boron-phosphorus-aluminum composition, clay and pseudo-boehmite;

[0028] The molecular sieve is added into water and sheared, and then added into the catalyst matrix slurry, and rare earth compound and dispersant are added, slurried, and then spray-formed, roasted, washed and dried to obtain the catalytic cracking catalyst.

[0029] More preferably, the aging temperature is 40 to 90° C., further preferably 75° C., and the aging time is 1 to 5 hours, further preferably 1 hour.

[0030] In the preparation process of the catalytic cracking catalyst, when the first raw material is mixed with water for slurrying, the solid content of the system is preferably 10wt% to 45wt%. The calcination temperature of the catalytic cracking catalyst is preferably 400 to 800°C, and the time is preferably 0.5 to 3h; more preferably, calcination at 500°C for 1 hour. The drying temperature is preferably 80 to 150°C, and the time is preferably 5 to 24h. The washing is performed by water washing.

[0031] In the process of preparing the catalytic cracking catalyst, preferably, the corresponding raw materials of each component in the obtained catalytic cracking catalyst, calculated on a dry basis of oxides, have a molecular sieve content of 20wt% to 50wt%, a borophosphorus-aluminum composition content of 5wt% to 25wt%, a clay content of 18wt% to 45wt%, a pseudo-boehmite content of 0 to 13wt%, a binder content of 8wt% to 15wt%, a rare earth element content of 0.5wt% to 10wt%, and a dispersant content of 1wt% to 10wt%.

[0032] In the process of preparing the catalytic cracking catalyst, preferably, the molecular sieve is selected from one or a combination of two or more of RDSY molecular sieve, REY molecular sieve, β molecular sieve and ZSM-5 molecular sieve.

[0033] In the process of preparing the catalytic cracking catalyst, preferably, the clay is selected from one or a combination of two or more of kaolin, etalonite, montmorillonite and attapulgite.

[0034] In the process of preparing the catalytic cracking catalyst, preferably, the binder is selected from one or a combination of two or more of aluminum sol, silica sol or colloidal aluminum oxide or silicon oxide materials.

[0035] In the catalytic cracking catalyst preparation process, preferably, the rare earth compound is a nitrate or carbonate of lanthanum or cerium.

[0036] In the process of preparing the catalytic cracking catalyst, preferably, the dispersant is one or a combination of two or more of citric acid, tartaric acid, C2-8 alcohol, polyethylene glycol, cellulose derivatives, polyacrylamide and its derivatives, and guar gum. More preferably, the cellulose derivative is selected from sodium hydroxymethylcellulose, methyl hydroxyethyl cellulose, and hydroxypropyl methylcellulose; and the C2-8 alcohol is selected from ethanol, ethylene glycol, glycerol, isopropanol, n-propanol, and 1,3-butanediol.

[0037] The second aspect of the present invention provides a metal-resistant catalytic cracking catalyst prepared by any of the above preparation methods.

[0038] According to the metal-resistant catalytic cracking catalyst of the present invention, preferably, the content of the boron-phosphorus-aluminum composition is 1 wt% to 30 wt% of the raw materials corresponding to the components in the catalytic cracking catalyst, calculated on a dry oxide basis.

[0039] According to the metal-resistant catalytic cracking catalyst of the present invention, preferably, the content of the clay in the corresponding raw materials of the components in the catalytic cracking catalyst is 18 wt% to 45 wt% on a dry basis of oxides.

[0040] According to the metal-resistant catalytic cracking catalyst of the present invention, preferably, the components in the catalytic cracking catalyst correspond to raw materials, and the content of the pseudo-boehmite is 0 to 13 wt % calculated on a dry oxide basis.

[0041] According to the metal-resistant catalytic cracking catalyst of the present invention, preferably, the content of the binder is 8 wt% to 15 wt% based on the raw materials of each component in the catalytic cracking catalyst, calculated on a dry oxide basis.

[0042] According to the metal-resistant catalytic cracking catalyst of the present invention, preferably, the content of the molecular sieve in the corresponding raw materials of each component in the catalytic cracking catalyst is 20wt% to 50wt% on a dry oxide basis.

[0043] According to the metal-resistant catalytic cracking catalyst of the present invention, preferably, the content of rare earth elements in the components corresponding to the raw materials in the catalytic cracking catalyst is 0.5wt% to 10wt% on a dry oxide basis.

[0044] According to the metal-resistant catalytic cracking catalyst of the present invention, preferably, the content of the dispersant is 1 wt% to 10 wt% of the raw materials of each component in the catalytic cracking catalyst, calculated on a dry oxide basis.

[0045] The present invention adds a boron-phosphorus-aluminum composition as an additive component to the catalyst preparation to obtain a catalytic cracking catalyst resistant to metal pollution. The composition is a mixture of AlPO4 and B, P, and Al. The B element can effectively combine with nickel, effectively convert nickel into a relatively stable compound, reduce the dehydrogenation activity of nickel, reduce the poisoning effect of nickel on the catalytic cracking catalyst, effectively reduce the yield of hydrogen and coke, and increase the yield of high value-added products. The presence of AlPO4 can effectively inhibit the dealumination of the molecular sieve, offset the poisoning effect of the addition of B and V in the device on the catalyst, and the AlPO4 with a relatively large specific surface and the loose and porous structure of the catalyst can fix Fe on its surface, effectively prevent the flow of Fe, and reduce the poisoning effect of the Fe element on the catalyst. A rare earth compound that can fix the V element is also added to the catalyst, which can effectively capture the V element, thereby reducing the poisoning effect of V on the catalyst.

[0046] During the preparation of the boron-phosphorus-aluminum composite, boron is fixed in the pores of the composite through the formation of a mesoporous structure through calcination. During the preparation of the catalyst, it is not easy to migrate to the surface of the molecular sieve and destroy the skeleton structure of the molecular sieve, so that the catalyst can maintain a relatively high activity stability. DETAILED DESCRIPTION

[0047] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the content described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0048] All numerical specifications herein (e.g., temperature, time, concentration, and weight, etc., including ranges for each thereof) are generally approximate values ​​that may be appropriately varied (+) or (-) in increments of 0.1 or 1.0. All numerical specifications may be understood as being preceded by the term "about."

[0049] The raw materials and properties used in the following examples are:

[0050] Kaolin, silica sol (solid content of 40wt%), alumina sol (solid content of 18.0wt%), various molecular sieves, pseudo-boehmite (dry basis is the part after ignition loss, and its molecular weight is 101.96) and hydrochloric acid (30wt%) are all of industrial grade; nickel nitrate, boric acid, boric anhydride, aluminum nitrate, aluminum chloride, ammonium metavanadate, oxalic acid, cerium nitrate, cerium carbonate, lanthanum oxide, glycerol, ethylene glycol, isopropanol, n-propanol, 1,3-butanediol, methyl hydroxyethyl cellulose, hydroxypropyl methylcellulose, sodium hydroxymethyl cellulose are of analytical grade; phosphoric acid 85wt%.

[0051] Catalyst micro-reaction activity evaluation method: The micro-reaction activity evaluation device developed by Beijing Huier Sanji Green Chemical Technology Co., Ltd. was used for evaluation. The raw oil used was 3 million tons / year of catalyst from Lanzhou Petrochemical Company. The properties of the raw oil are shown in Table 1. The catalyst was aged at 800°C and 100% steam for 17 hours before evaluation.

[0052] Catalyst reaction performance evaluation method:

[0053] The catalyst was contaminated with heavy metals before evaluation. The method of heavy metal contamination simulated the content of nickel and V in industry: the aqueous solution of nickel nitrate, ferric cyclopentaneate solution, ammonium metavanadate and oxalic acid composite solution (10000ppm Ni, 3000ppm V, 6000ppm Fe based on the dry basis of the catalyst) was impregnated into the catalyst using the Mitchell method, dried at 120℃, and calcined at 550℃ for 4 hours. The reaction performance was evaluated using the ACE device. The raw oil used was the 3 million tons / year catalyst of Lanzhou Petrochemical Company. The properties of the raw oil are shown in Table 1. The catalyst was aged at 800℃ and 100% steam for 8h before evaluation.

[0054] Table 1 Raw oil properties

[0055]

[0056] Preparation of boron-phosphorus-aluminum composition:

[0057] Composition 1

[0058] 2129.96 g of aluminum nitrate (Al: 10 mol) was added to 3 L of water under stirring until dissolved, 1152.94 g of 85 wt% phosphoric acid (P: 10 mol) was added dropwise to the dissolved aluminum nitrate to form a homogeneous sol, and then 85.68 g of boric acid (B: 1.4 mol) was added and stirring was continued for 0.5 h. The sol was dried in an oven at 80 ° C for 24 h and calcined at 700 ° C for 1 h to obtain composition 1.

[0059] Composition 2

[0060] 1019.60 g of dry pseudo-boehmite (Al: 20 mol) was dispersed in 3 L of water under stirring and the stirring was continued for 0.5 h. 1400.00 g of 70 wt% phosphoric acid (P: 10 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 1 h. Then 219.30 g of boric anhydride (B: 6.3 mol) was added and the stirring was continued for 1 h. The sol was dried in an oven at 120 ° C for 5 h and calcined at 500 ° C for 2 h to obtain composition 2.

[0061] Composition 3

[0062] 1333.40 g of aluminum chloride (Al: 10 mol) was dissolved in 1 L of water under stirring, and 6533.33 g of 30 wt% phosphoric acid (P: 20 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 2 h, and then 653.18 g of ammonium borate (B: 10.54 mol) was added. The stirring was continued for 1 h. The sol was dried in an oven at 90 ° C for 10 h and calcined at 450 ° C for 3 h to obtain composition 3.

[0063] Composition 4

[0064] 2129.96 g of aluminum nitrate (Al: 10 mol) was added to 2 L of water under stirring until dissolved, 1633.33 g of 40 wt% phosphoric acid (P: 6.7 mol) was added dropwise to the dissolved aluminum nitrate to form a homogeneous sol, and then 281.05 g of ammonium fluoroborate (B: 2.7 mol) was added and stirring was continued for 0.5 h. The sol was dried in an oven at 110 ° C for 15 h and calcined at 400 ° C for 4 h to obtain composition 4.

[0065] Composition 5

[0066] 1333.40 g aluminum chloride (Al: 10 mol) was dissolved in 1 L water under stirring, and 6533.33 g 30 wt% phosphoric acid (P: 20 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 2 h. The sol was dried in an oven at 120°C for 10 h and ground into powder.

[0067] 217.28 g of boric acid (B: 3.51 mol) was dissolved in 500 mL of water, added to the above powder and immersed for 1 h, dried at 120° C. for 5 h, and calcined at 450° C. for 3 h to obtain composition 5.

[0068] Comparative composition 1

[0069] 1019.60 g of dry pseudo-boehmite (Al: 20 mol) was dispersed in 3 L of water under stirring, and stirring was continued for 0.5 h. 1960.00 g of 50 wt% phosphoric acid (P: 10 mol) was added dropwise under stirring, and stirring was continued for 1 h. Then 274.11 g of boric anhydride (B: 7.9 mol) was added, and stirring was continued for 1 h. The sol was dried in an oven at 100 ° C for 12 h to obtain a comparative composition 1.

[0070] Comparative composition 2

[0071] 2129.96 g aluminum nitrate (Al: 10 mol) was added to 3 L water under stirring until dissolved, and then 61.83 g boric acid (B: 1 mol) was added and stirring was continued for 0.5 h. The mixture was dried in an oven at 80 ° C for 24 h and calcined at 700 ° C for 1 h to obtain comparative composition 2.

[0072] Comparative composition 3

[0073] 1019.60 g of dry pseudo-boehmite (Al: 20 mol) was dispersed in 3 L of water under stirring and the stirring was continued for 0.5 h. 1400.00 g of 70 wt% phosphoric acid (P: 10 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 1 h. The sol was dried in an oven at 120 ° C for 5 h and calcined at 500 ° C for 2 h to obtain comparative composition 3.

[0074] The compositions and some preparation conditions of the above compositions 1-5 and comparative compositions 1-3 are shown in Table 2.

[0075] Table 2 Compositions and preparation conditions of compositions 1-5 and comparative compositions 1-3

[0076]

[0077] Example 1

[0078] This example uses composition 1 to prepare catalytic cracking catalyst S1, comprising the following steps:

[0079] In a reactor with water bath heating, add 2.5L water, 1335g attapulgite, 150g pseudo-boehmite, 600g composition 1, then slowly add 90g hydrochloric acid and mix evenly. After stirring for 1 hour, age at 75°C for 1h, and then add 1666g aluminum sol to form a catalyst matrix slurry; add 2L water to a pulping tank, add 600g β molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, add 37.83g cerium nitrate hexahydrate and 30.0g propylene glycol, after pulping for 1h, spray molded, the obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried at 150°C for 5h to obtain catalyst S1.

[0080] Example 2

[0081] This example uses composition 2 to prepare catalytic cracking catalyst S2, comprising the following steps:

[0082] In a reactor with water bath heating, add 2L of water, 750g of montmorillonite, and 750g of composition 2, mix well, stir for 1 hour, age at 75°C for 1h, and then add 1833g of aluminum sol to form a catalyst matrix slurry; add 1.7L of water to a pulping tank, add 980g of RDSY+100g of REY molecular sieves, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, add 110.8g of cerium carbonate, 60.0g of methyl hydroxyethyl cellulose and 60.0g of ethylene glycol, pulp for 1h, and then spray mold. The obtained microspheres are calcined at 400°C for 3 hours, washed with water, and dried at 120°C for 16h to obtain catalyst S2.

[0083] Example 3

[0084] This example uses composition 3 to prepare catalytic cracking catalyst S3, comprising the following steps:

[0085] In a reactor with water bath heating, 3.5L water, 660g halloysite, 150g composition 3, 390g pseudo-boehmite were added and mixed evenly, 190g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1h, and then 1333g aluminum sol was added to form a catalyst matrix slurry; 4L water was added to a pulping tank, 900g RDSY+600g ZSM-5 molecular sieve was added, and after passing through a high-speed shearing machine for 20min, it was added to the catalyst matrix slurry, 60.0g cerium oxide, 120g sodium hydroxymethyl cellulose and 60g isopropanol were added, and after pulping for 1h, it was spray-formed, and the obtained microspheres were calcined at 800°C for 0.5h, washed with water, and dried at 110°C for 24h to obtain catalyst S3.

[0086] Example 4

[0087] This embodiment uses composition 4 to prepare catalytic cracking catalyst S4, comprising the following steps:

[0088] In a reactor with water bath heating, 2.5L water, 1020g kaolin, 300g composition 4, and 180g pseudo-boehmite were added and mixed evenly, 90g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1h, and then 1333g aluminum sol was added to form a catalyst matrix slurry; 3.5L water was added to a pulping tank, 1080g RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20min, it was added to the catalyst matrix slurry, 271.0g lanthanum chloride, 100g n-propanol and 140.0g hydroxypropyl methylcellulose were added, and after pulping for 1h, it was spray-formed, and the obtained microspheres were calcined at 700°C for 1 hour, washed with water, and dried at 80°C for 24h to obtain catalyst S4.

[0089] Example 5

[0090] This embodiment uses composition 5 to prepare catalytic cracking catalyst S5, comprising the following steps:

[0091] In a reactor with water bath heating, 3.5L water, 540g kaolin, 390g composition 5, and 240g pseudo-boehmite were added and mixed evenly, 120g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 1125g silica sol was added to form a catalyst matrix slurry; 3.0L water was added to a pulping tank, 1080g RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20 minutes, it was added to the catalyst matrix slurry, 598.3g lanthanum nitrate and 200.0g 1,3-butanediol were added, and after pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 100°C for 20 hours to obtain catalyst S5.

[0092] Example 6

[0093] This example uses composition 2 to prepare catalytic cracking catalyst S6, comprising the following steps:

[0094] In a reactor with water bath heating, 4L of water, 810g of kaolin, 4240g of composition 2, and 270g of pseudo-boehmite were added and mixed evenly, 130g of hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 900g of silica sol was added to form a catalyst matrix slurry; 4L of water was added to a pulping tank, 1080g of RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20 minutes, it was added to the catalyst matrix slurry, 337.3g of lanthanum carbonate and 90g of hydroxymethyl cellulose were added, and after pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 16 hours to obtain catalyst S6.

[0095] Comparative Example 1

[0096] This comparative example prepares catalytic cracking catalyst D1, in which no boron-phosphorus-aluminum composition is used, comprising the following steps:

[0097] In a reactor with water bath heating, add 2.5L water, 1470g kaolin, 150g pseudo-boehmite, and then slowly add 90g hydrochloric acid to mix evenly. After stirring for 1 hour, age at 75°C for 1h, and then add 1666g aluminum sol to form a catalyst matrix slurry; add 2L water to a pulping tank, add 1080g RDSY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold. The obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried at 130°C for 16h to obtain catalyst D1.

[0098] Comparative Example 2

[0099] This comparative example prepares catalytic cracking catalyst D2, wherein boric acid is used instead of the boron-phosphorus-aluminum composition, comprising the following steps:

[0100] In a reactor with water bath heating, add 2.5L water, 1470g kaolin, 150g pseudo-boehmite, 422g boric acid, then slowly add 90g hydrochloric acid and mix evenly. After stirring for 1 hour, age at 75°C for 1h, and then add 1666g aluminum sol to form a catalyst matrix slurry; add 2L water to a pulping tank, add 1080g RDSY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold. The obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 16h to obtain catalyst D2.

[0101] Comparative Example 3

[0102] This comparative example uses comparative composition 1 to prepare catalytic cracking catalyst D3, comprising the following steps:

[0103] In a reactor with water bath heating, 2.5L water, 1020g kaolin, 300g comparison composition 1, and 180g pseudo-boehmite were added and mixed evenly, 90g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1h, and then 1333g aluminum sol was added to form a catalyst matrix slurry; 3.5L water was added to a pulping tank, 1080g RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20min, it was added to the catalyst matrix slurry, 271.0g lanthanum chloride, 100g n-propanol and 140.0g hydroxypropyl methylcellulose were added, and after pulping for 1h, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 16h to obtain catalyst D3.

[0104] Comparative Example 4

[0105] This comparative example prepares catalytic cracking catalyst D4, wherein a sol containing boron, phosphorus and aluminum is used instead of the boron-phosphorus-aluminum composition of the present invention, comprising the following steps:

[0106] 1155.61 g of aluminum chloride was dissolved in 1 L of water under stirring, and 2426.65 g of 70 wt% phosphoric acid and 306.8 g of boric acid were added dropwise under stirring to form a homogeneous sol. Stirring was continued for 2 h to obtain Sol A.

[0107] In a reactor with water bath heating, 1.7L water, 540g kaolin, and 240g pseudo-boehmite were added and mixed evenly, 120g hydrochloric acid was added dropwise, and after stirring for 1 hour, the above-obtained sol A was added, aged at 75°C for 1h, and then 1125g silica sol was added to form a catalyst matrix slurry; 3.0L water was added to a pulping tank, 1080g RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20min, it was added to the catalyst matrix slurry, 598.3g lanthanum nitrate and 200.0g 1,3-butanediol were added, and after pulping for 1h, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 16h to obtain catalyst D4.

[0108] Comparative Example 5

[0109] This comparative example uses comparative composition 2 to prepare catalytic cracking catalyst D5, comprising the following steps:

[0110] In a reactor with water bath heating, 2.5L of water, 1020g of kaolin, 300g of comparison composition 2, and 180g of pseudo-boehmite were added and mixed evenly, 90g of hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1h, and then 1333g of aluminum sol was added to form a catalyst matrix slurry; 3.5L of water was added to a pulping tank, 1080g of RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20min, it was added to the catalyst matrix slurry, 271.0g of lanthanum chloride, 100g of n-propanol and 140.0g of hydroxypropyl methylcellulose were added, and after pulping for 1h, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 16h to obtain catalyst D5.

[0111] Comparative Example 6

[0112] This comparative example uses comparative composition 3 to prepare catalytic cracking catalyst D6, comprising the following steps:

[0113] In a reactor with water bath heating, 2.5L water, 1020g kaolin, 300g comparison composition 3, and 180g pseudo-boehmite were added and mixed evenly, 90g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1h, and then 1333g aluminum sol was added to form a catalyst matrix slurry; 3.5L water was added to a pulping tank, 1080g RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20min, it was added to the catalyst matrix slurry, 271.0g lanthanum chloride, 100g n-propanol and 140.0g hydroxypropyl methylcellulose were added, and after pulping for 1h, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 16h to obtain catalyst D6.

[0114] Comparative Example 7

[0115] This comparative example prepares catalytic cracking catalyst D7, wherein boric acid and phosphoric acid (both account for 15wt% of the dry content of the catalyst) are used instead of the boron-phosphorus-aluminum composition of the present invention, comprising the following steps:

[0116] In a reactor with water bath heating, 2.5L of water, 960g of kaolin, 180g of pseudo-boehmite, and 422g of boric acid were added and mixed evenly, 90g of hydrochloric acid was added, and after stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1333g of aluminum sol was added to form a catalyst matrix slurry; 3.5L of water was added to a beating tank, 1080g of RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry, 271.0g of lanthanum chloride, 100g of n-propanol and 140.0g of hydroxypropyl methylcellulose were added, and 358g of 85wt% phosphoric acid was added. After beating for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 16 hours to obtain catalyst D7.

[0117] The compositions of the raw materials corresponding to the components of the above catalysts S1-S6 and D1-D7 are shown in Table 3 below, the activity data are shown in Table 4 below, and the ACE evaluation results of the contaminated samples of each catalyst (contaminated with 12000 ppm nickel) are shown in Table 5.

[0118] Table 3 Composition of raw materials corresponding to each component in the catalyst obtained in the examples and comparative examples (on a dry basis of oxides)

[0119]

[0120] Note: The dispersant is removed during the calcination process and therefore does not contribute to the dry weight of the catalyst.

[0121] Table 4 Catalyst activity (MAT, 800℃×17h)

[0122] Catalyst No. S1 S2 S3 S4 S5 S6 D1 D2 D3 D4 D5 D6 D7 Catalyst activity 61 62 63 64 63 65 62 56 58 58 58 63 60

[0123] As can be seen from Table 4, the catalysts S1-S6 of the embodiment still have relatively high activity after 800°C×17h water vapor aging, while the activity of the catalysts D2, D3, D4, D5, and D7 of the comparative examples decreases significantly, indicating that the addition method of boron (B) has an effect on the structure of the molecular sieve. The presence of AlPO4 in the boron-phosphorus-aluminum composition of the present invention can effectively inhibit the dealumination of the molecular sieve and offset the toxic effect of the addition of B on the catalyst. At the same time, during the preparation of the boron-phosphorus-aluminum composition, a mesoporous structure is formed by roasting, and boron is fixed in the pores of the composition. It is not easy to migrate to the surface of the molecular sieve during the preparation of the catalyst, destroying the skeleton structure of the molecular sieve, so that the catalysts S1-S6 can still maintain relatively high activity stability after 800°C×17h water vapor aging. Catalyst D2 uses boric acid instead of the boron-phosphorus-aluminum composition, catalyst D3 uses the uncalcined comparative composition 1, catalyst D4 uses a sol containing boron, phosphorus and aluminum instead of the boron-phosphorus-aluminum composition of the present invention, D5 uses the phosphorus-free comparative composition 2 instead of the boron-phosphorus-aluminum composition, and D7 uses phosphoric acid and boric acid instead of the boron-phosphorus-aluminum composition, all of which show a significant decrease in activity. Catalyst D1 does not add any composition or other B substitutes as a blank control, and D6 uses the boron-free comparative composition 3.

[0124] Table 5 ACE evaluation results of various catalyst contaminated samples

[0125]

[0126] As can be seen from Table 5, after the catalyst was contaminated with 10000ppm nickel, 3000ppm vanadium, and 5000ppm iron, the conversion rate of the catalyst sample of the embodiment was relatively high, and the H2 / CH4 ratio was relatively low compared to the catalyst D1 of the comparative example, indicating that the addition of the boron-phosphorus-aluminum composition of the present invention has certain anti-metal properties. Compared with comparative examples D2, D4, and D7, the embodiment has a relatively high conversion rate, indicating that the addition of the boron-phosphorus-aluminum composition can significantly reduce the toxic effect of B on the molecular sieve; compared with comparative example D3, the embodiment has a relatively high conversion rate and a better product distribution, indicating that the step of roasting the boron-phosphorus-aluminum composition is very critical; compared with D5 and D6, the embodiment has a relatively high conversion rate and a better product distribution, indicating that the phosphorus and boron elements in the boron-phosphorus-aluminum composition play a key role in resisting the pollution of heavy metals nickel, vanadium, and iron.

[0127] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a metal-resistant catalytic cracking catalyst, wherein: The preparation method comprises the following steps: The first raw material is mixed with water and slurried; a rare earth compound and a dispersant are added to the slurry and stirred evenly; and then the catalytic cracking catalyst is obtained by spray molding, roasting, washing and drying; The first raw material includes a boron-phosphorus-aluminum composition, a molecular sieve, clay and a binder; The boron-phosphorus-aluminum composite is a mixture of AlPO4 and B, P, and Al, and is calcined during the preparation process.

2. The preparation method according to claim 1, wherein The first raw material also includes pseudo-boehmite.

3. The preparation method according to claim 1, wherein The boron-phosphorus-aluminum composite is prepared by reacting an aluminum compound, phosphoric acid, and a boron compound and calcining at 400-700°C; The boron compound is added according to the boron content of 2wt% to 6wt% in the total mass of the boron-phosphorus-aluminum composition; The aluminum compound and phosphoric acid are added in a molar ratio of Al:P of (0.5-2.0):

1.

4. The preparation method according to claim 3, wherein The boron-phosphorus-aluminum composition is prepared by the following method 1 or method 2: Method 1: Add aluminum compound to water, then add phosphoric acid dropwise; then add boron compound and stir to obtain a sol containing boron, phosphorus and aluminum; Drying the sol containing boron, phosphorus and aluminum, and calcining at 400-700° C. for 1 h-4 h to obtain the boron-phosphorus-aluminum composite; Method 2: adding an aluminum compound to water, and then dropping phosphoric acid to obtain a sol containing phosphorus and aluminum; drying the sol containing phosphorus and aluminum to obtain an intermediate product; The boron compound is dissolved in water, loaded in the intermediate product by an impregnation method, dried, and calcined at 400 to 700° C. for 1 to 4 hours to obtain the boron-phosphorus-aluminum composite.

5. The preparation method according to claim 3 or 4, wherein The aluminum compound is selected from one or a combination of two or more of aluminum oxide, pseudo-boehmite, aluminum nitrate, and aluminum chloride.

6. The preparation method according to claim 3 or 4, wherein: The boron compound is selected from one or a combination of two or more of boron phosphate, boric acid, boric anhydride, ammonium borate, and ammonium fluoroborate.

7. The preparation method according to any one of claims 1 to 4, wherein: The specific preparation process of the catalytic cracking catalyst includes: Adding the second raw material into water, mixing evenly, and then adding a binder after aging to form a catalyst matrix slurry; the second raw material includes the boron-phosphorus-aluminum composition and clay, or the second raw material includes the boron-phosphorus-aluminum composition, clay and pseudo-boehmite; The molecular sieve is added into water and sheared, and then added into the catalyst matrix slurry, and rare earth compound and dispersant are added, slurried, and then spray-formed, roasted, washed and dried to obtain the catalytic cracking catalyst.

8. The preparation method according to claim 1, wherein The calcination temperature of the catalytic cracking catalyst is 400-800° C., and the calcination time is 0.5-3 hours.

9. The preparation method according to claim 2, wherein: The corresponding raw materials of each component in the obtained catalytic cracking catalyst are calculated on a dry basis as follows: the content of the molecular sieve is 20wt% to 50wt%, the content of the boron-phosphorus-aluminum composition is 5wt% to 25wt%, the content of the clay is 18wt% to 45wt%, the content of the pseudo-boehmite is 0 to 13wt%, the content of the binder is 8wt% to 15wt%, the content of the rare earth element is 0.5wt% to 10wt%, and the content of the dispersant is 1wt% to 10wt%.

10. The preparation method according to claim 1, wherein: The molecular sieve is selected from one or a combination of two or more of RDSY molecular sieve, REY molecular sieve, β molecular sieve and ZSM-5 molecular sieve.

11. The preparation method according to claim 1, wherein: The clay is selected from one or a combination of two or more of kaolin, elosite, montmorillonite and attapulgite.

12. The preparation method according to claim 1, wherein: The binder is selected from one or a combination of two or more of aluminum sol, silica sol or colloidal aluminum oxide or silicon oxide materials.

13. The preparation method according to claim 1, wherein: The rare earth compound is nitrate or carbonate of lanthanum or cerium.

14. The preparation method according to claim 1, wherein: The dispersant is one or a combination of two or more of citric acid, tartaric acid, C2-8 alcohol, polyethylene glycol, cellulose derivatives, polyacrylamide and its derivatives, and guar gum.

15. The preparation method according to claim 14, wherein: The cellulose derivative is selected from sodium hydroxymethylcellulose, methyl hydroxyethyl cellulose, and hydroxypropyl methylcellulose; The C2-8 alcohol is selected from ethanol, ethylene glycol, glycerol, isopropanol, n-propanol, and 1,3-butanediol.

16. A metal-resistant catalytic cracking catalyst prepared by the preparation method according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Anti-heavy-metal catalytic cracking catalyst and preparation method

    CN105728031A

  • Heavy oil catalytic cracking catalyst and preparation method thereof

    CN111686785A

  • Preparation method of heavy metal-resistant catalytic cracking catalyst

    CN112108171A

  • Heavy oil catalytic conversion method

    CN115141649A

  • Catalytic cracking catalyst, preparation method therefor, and application thereof

    WO2022063203A1